Asymptomatic rupture of cornual gestation presented as abdominal mass - Saichandran, Sabita; Samal, Sunita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
We report a case of mass abdomen secondary to asymptomatic rupture of cornual pregnancy probably occurred 1-2 months prior to her visit. Uterus sparing surgery was performed following which she had spontaneous conception in less than a year with successful outcome.